1998
DOI: 10.1007/s001250051022
|View full text |Cite
|
Sign up to set email alerts
|

Decreased stature in gestational diabetes mellitus

Abstract: Adult height is determined by genetic and acquired factors. It has been reported that middle-aged patients with impaired glucose tolerance or Type II (non-insulin-dependent) diabetes mellitus are short compared with normal control subjects [1,2]. In middle-aged diabetic patients it is, however, difficult to exclude the effect of ageing and long standing metabolic effects on height.There is a lot of evidence that Type II diabetes and gestational diabetes mellitus (GDM) are both manifestations of the same pathop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
51
1
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 14 publications
(7 reference statements)
6
51
1
2
Order By: Relevance
“…Although publication bias cannot be ruled out, the challenge in including short stature as a risk factor for gestational diabetes mellitus seems to be the definition of the cut-off point for this variable. In Brazil, based on the Brazilian Gestational Diabetes Study (EBDG), the study of Branchtein et al 27 defined it as ≤ 151cm, however studies in other countries observed associations using different height categories 21,25,26,29,33 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although publication bias cannot be ruled out, the challenge in including short stature as a risk factor for gestational diabetes mellitus seems to be the definition of the cut-off point for this variable. In Brazil, based on the Brazilian Gestational Diabetes Study (EBDG), the study of Branchtein et al 27 defined it as ≤ 151cm, however studies in other countries observed associations using different height categories 21,25,26,29,33 .…”
Section: Discussionmentioning
confidence: 99%
“…The association remained regardless of age, weight and pre-pregnancy BMI, family history of diabetes mellitus, parity and weight gain during pregnancy. Anastasiou et al 26 , evaluating a cohort of pregnant Greek women referred to a service for screening of diabetes, found that the mean height among pregnant women with gestational diabetes mellitus was significantly lower than among those without gestational diabetes mellitus. Such findings remained true even after stratification by weight, maternal schooling and cohort effect.…”
Section: Heightmentioning
confidence: 99%
“…This notion is supported by the observation of a higher risk of developing type 2 diabetes in men than in women with i-IGT [7], indicating that women with i-IGT may be healthier than their male counterparts. Moreover, women are more commonly diagnosed with diabetes on the basis of 2 h post-OGTT plasma glucose (2hPG) levels compared with fasting plasma glucose (FPG) levels [8], and the risk of gestational diabetes is higher in shorter compared with taller women [9].…”
Section: Introductionmentioning
confidence: 99%
“…Os principais fatores reconhecidos até o momento são: história familiar de diabetes em familiar de primeiro grau, obesidade, idade superior a 25 anos, hipertensão arterial sistê-mica, mau passado obstétrico (antecedentes obstétricos de morte fetal ou neonatal, história de macrossomia fetal ou diabetes gestacional prévios, abortos de repetição e malformações congênitas fetais) e macrossomia, polidrâmnio, doença hipertensiva específica da gestação (DHEG) ou ganho de peso excessivo na gestação em curso (5). Mais recentemente, a baixa estatura da gestante (≤ 151 cm) e a síndrome dos ovários policísticos (SOP) também foram descritas como fatores de risco para DMG (6,7).…”
unclassified